Motion- and orientation-specific cortical responses in infancy. - Braddick, O; Birtles, D; Wattam-Bell, J; Atkinson, J (2005)
During the first 3 months, infants develop visual evoked potential (VEP) responses that are signatures of cortical orientation-selectivity and directional motion selectivity. Orientation-specific cortical responses develop in early infancy. This study compared these responses directly in the same infants, to investigate whether the later appearance of direction selectivity was intrinsic, or a function of the spatio-temporal characteristics of the stimuli used. Steady-state orientation-reversal (OR-) VEPs and direction-reversal (DR-) VEPs were recorded in infants aged 4-18 weeks. DR-VEPs were elicited with random pixel patterns and with gratings spatially similar to those used for OR-VEPs, at velocities of 5.5 and 11 deg/s, and reversal rates of 2 and 4 reversals/s. Infants throughout the age range showed significant responses to orientation-reversal. Direction-reversal responses appeared in less than 25% of infants under 7 weeks of age, rising to 80% or more at 11-13 weeks, whether tested with dots or gratings and for both speeds and reversal rates. However, 2 reversals/s elicits the DR-VEP on average about 2 weeks earlier than 4 reversal/s stimulation. We conclude that human cortical direction selectivity develops separately from orientation-selectivity and emerges at a later age, even with tests that are designed to optimise the former.